2022
DOI: 10.3233/shti210945
|View full text |Cite
|
Sign up to set email alerts
|

Using Automated Text Processing to Assess the Patient Experience of an On-Demand Tele-Urgent Care

Abstract: Novel methods are needed to evaluate the perceptions of patients using telehealth. Automated text processing methods presents a golden opportunity to classify and analyze unstructured survey responses from patients. This study analyzed 585 unstructured entries from telehealth patients. Satisfied patients who returned for a second visit applauded the efficiency and physician interactions. While unsatisfied patients who did not return for a second visit complained of misdiagnosis and inefficiencies in e-prescrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…In addition, we found that patients’ overall satisfaction level was an indicator of their preferred choice of modality in the future, as we would expect; such that lower telemedicine satisfaction was associated with patients’ choosing to be seen in-person for future appointments. Our findings among incarcerated individuals concur prior studies involving the general public showing that telemedicine prior experiences were associated with lower satisfaction levels (14,15).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we found that patients’ overall satisfaction level was an indicator of their preferred choice of modality in the future, as we would expect; such that lower telemedicine satisfaction was associated with patients’ choosing to be seen in-person for future appointments. Our findings among incarcerated individuals concur prior studies involving the general public showing that telemedicine prior experiences were associated with lower satisfaction levels (14,15).…”
Section: Discussionsupporting
confidence: 90%